Developing A Creative Economic-Based Village Tourism In Kendran Village Gianyar Regency - Arismayanti, Ni Ketut; Widyatmaja, I Gusti Ngurah; Wiraatmaja, I Wayan (Journal of A Sustainable Global South; Vol 3 No 1 (2019): February 2019DO - 10.24843/jsgs.2019.v03.i01.p01, 2019)
This research aims to identify the potential of natural tourism, cultural tourism, and creativity of local communities of Kendran Village and determine the condition of the internal environment (as seen from the strengths and weaknesses) and external environment (as seen from the opportunities and threats) of Kendran Village since the development of creative-economy based village tourism is one of the attempts to open up the market share (market niche) that had not been done yet. SWOT analysis method was used in this research to explore the potential of the internal environment, such as Strengths, namely rice field scenery with jogging tracks, the preserved traditional culture as traditional Balinese architecture, sacred places, historical relics in the village area, the activities of the Balinese-Hinduism ceremonies, arts and cultures, as well as the hospitality of communities, and accessible areas. We found the weaknesses on infrastructure, public facilities, lack of tourism programs along with its management, and lack of foreign languages including English. Likewise, on the external environment, they have the opportunities in location of Kendran Village, the popularity of village tourism, increasing of tourists arrival who are interested in culture & natural tourism, information and technological advances that support the promotion of Kendran Village, the support of the Gianyar Government, the development of creative-economy based tourism, and the threats such as increased competition in tourism industry, lack of passion of rural life in young generations, the culture commercialization, and also the stability of political and security situation in Indonesia. Index Terms — natural potentials, cultural potentials, creative local community, creative economy.